2019
DOI: 10.3889/oamjms.2019.849
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Left Ventricular Systolic Function in Patients Undergoing Coronary Artery Bypass Grafting

Abstract: AIM: This prospective study was designed to evaluate the changes in left ventricular (LV) systolic function after coronary artery bypass grafting (CABG) in patients with both normal and abnormal pre-operative systolic function. METHODS: During the period from October 2017 to October 2018, forty-seven consecutive patients undergoing CABG were enrolled in this prospective study. Transthoracic echocardiography was performed within 1 week before CABG as well as 4 to 6 months after surgery. All measurements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Papestiev et al, prospectively evaluated 47 patients (27 with preoperative LVEF >50%) and found that ΔLVEF >5% occurred in 53.2% of patients. LVEF improvement of >5% was significantly more likely if LVEF <50%, and preoperative LVEF was inversely associated with perioperative LVEF improvement [6]. Similarly, in two cohort studies limited to preoperative LVEF <35%, CABG was associated with increases in LVEF [18,19].…”
Section: Plos Onementioning
confidence: 87%
See 2 more Smart Citations
“…Papestiev et al, prospectively evaluated 47 patients (27 with preoperative LVEF >50%) and found that ΔLVEF >5% occurred in 53.2% of patients. LVEF improvement of >5% was significantly more likely if LVEF <50%, and preoperative LVEF was inversely associated with perioperative LVEF improvement [6]. Similarly, in two cohort studies limited to preoperative LVEF <35%, CABG was associated with increases in LVEF [18,19].…”
Section: Plos Onementioning
confidence: 87%
“…Finally, within a cohort with LVEF <50% (mean LVEF = 32%), Cornel et al observed a ΔLVEF >5% in 19% of patients at 3 months, which increased to 31% at twelve months [20]. Cumulatively, these prior works have shown LVEF improvement in patients who had preoperative LV systolic dysfunction but a higher risk of LVEF decline in individuals with a preoperatively normal LVEF [4][5][6][18][19][20].…”
Section: Plos Onementioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, the underlying pathology needs to be further investigated in such population. LV remodeling improved the outcomes of HF hospitalization and the value of baseline LVEF appeared as independent predictor of improved LVEF after CABG [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, for patients with a preserved baseline LVEF, research on the changes of LVEF after CABG is scarce. Papestiev et al reported that in patients with preoperative LV dysfunction, there is an improvement in systolic function, whereas, in patients with preserved preoperative myocardial function, a decline in postoperative LVEF was observed ( 22 ). This is consistent with our findings, which showed statistical differences in the non-single graft group and no statistical differences in the single graft group (not illustrated in table).…”
Section: Discussionmentioning
confidence: 99%